Antibacterial Activity Test of Ethanol Extract of Bitter Gourd Leaves (Momordica Charantia L) Against Acne-Causing Bacteria (Staphylococcus Epidermidis) - Ainur Rivda Silviyah; Arshy Prodyanatasari (Cigarskruie: Journal of Educational and Islamic Research, 2023)
Bitter melon leaves contain flavonoids, saponins, tannins and terpenoids, which have antibacterial potential. The aim of this research was to determine the antibacterial activity of an ethanol extract of bitter melon leaves. This antibacterial activity test was carried out using the disc diffusion method. The concentrations of bitter melon leaf ethanol extract used were 50%, 60%, and 70%. Clindamycin was used as a positive control and distilled water as a negative control. The data was obtained by using the one-way Anova statistical test. The test for antibacterial activity showed that the inhibitory zone was 9.07 mm wide at a 50% extract concentration, 10.72 mm wide at a 60% concentration, and 12.08 mm wide at a 70% concentration. The Sig value indicated that there was a significant difference between the positive control with extract concentrations of 50%, 60%, and 70%. 0.005. The ethanol extract of bitter melon has an inhibitory effect on the growth of Staphylococcus epidermidis bacteria.